I'M DYING TO BE A STAR: AN EXPLORATORY RESEARCH ON THE DEMAND IN SINGING COURSES IN PUBLIC SCHOOLS OF VOCATIONAL EDUCATION - Constantino, Paulo [UNESP]; Oliveira Poletine, Marcia Regina de (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Analyzes the significant increase in demand for the vocational education in Singing, in a Sao Paulo State public institution in recent years. Based on documentary research, combined with the analysis obtained with a focus group of new students in 2014, are considered some explanations for this demand. Expectations of fame and stardom - strongly nourished by the candidates - was initially investigated as the hypothesis.
Keywords: Singing courses; Demand in vocational educational; Public policies